ANTIMICROBIAL AND SOD-LIKE ACTIVITIES OF N,N′-BIS(FERROCENYLMETHYLENE)ETHYLENEDIAMINE SCHIFF BASE AND IT’S METAL COMPLEXES - Funda Demirhan; Hülya Avci Özbek; Tülin Aydemir; Mustafa Oskay; Seda Çinar (Journal of the Chilean Chemical Society, 2021)
The synthesized N,N′-bis(ferrocenylmethylene)ethylenediamine Schiff base and it’s metal complexes were screened in vitro for antimicrobial activity against two Gram-positive (Staphylococcus aureus ATCC 25923, Bacillus cereus ATCC 7064),four Gram-negative (Escherichia coli ATCC 25922, Citrobacter koseri DBCC 01, Entorebacter aeruginosa ATCC 13048,Salmonella typhimurium DBCC 02) and antifungal activity against a Candida albicans. MIC values of the compounds ranged from 27 to 533 µg/mL. Compound (5) showed very strong activity against S. aureus with the best MIC (27 µg/mL). The lowest MIC for C. albicans was obtained 107 µg/mL. The superoxide dismutase activity of Schiff base and it’s metal complexes has been measured and discussed. SOD-like activities of bis ferrocenyl Schiff base ligand metal complexes were investigated using NBT. While only the Cu (II) complex showed SOD-like (40 μm IC50) activity, the SOD-like activity value was not determined in the other complex and ligand.